Faster-than-Nyquist signaling: value and challenges of 6G-oriented applications - Xin SU; Sen WANG; Hongwen YANG; Jing JIN; Qixing WANG (Dianxin kexue)
The faster-than-Nyquist (FTN) signaling technology overlaps multiple streams of data within a symbol period by compressing the transmit symbol time/frequency-domain interval, thus breaking the orthogonality of the Nyquist pulse waveform and achieving the purpose of transmitting more data in a limited bandwidth.A relatively comprehensive explanation of the technical principles of FTN was elaborated, its development status was sorted out, and the related key questions——the relationship between FTN capacity and Shannon capacity, and the intrinsic connection of related technologies were answered.Finally, The possibility of FTN application in 6G was discussed, and its value and challenges in 6G were presented.That is, FTN is a highly spectrally efficient transmission scheme that approximates Shannon's capacity, but excessive receiver complexity may be a key impediment to its use in 6G applications.